Chapter Wetting and Navier-Stokes Equation - The Manufacture of Composite Materials - Caccia, Mario (InTechOpen, 2015)
Current landfill regulations provide for the responsible management of solid waste and a safer alternative to the outdated practices of open or illegal dumping. Aside from imparting aesthetic value, natural or planted vegetation on landfill sites has an important role in erosion control and removal of contaminants, and may also be used in leaching treatment. The use of leachate for the irrigation of landfill vegetation reduces its harmful effects, and the reuse of water aids in water conservation. The aim of this study was to search for ways to use leachate water from solid waste landfill sites for irrigation of plant species that normally grow in the wild. The study focuses on the plant species Alcea rosea (hollyhock), Cynodon dactylon (Bermuda grass) and Melilotus officinalis (yellow melilot). Over the 2-year study period, plants were irrigated with tap and leachate water under drought conditions. Wild plant diversity was identified, and the landfill was rehabilitated with various plant species. After the experiment, populations of Escherichia coli, total coliforms and fecal coliform bacteria in soil samples were analyzed. We observed that the use of leachate water for cultivation of different kinds of plants affected the density of total and fecal coliforms in the soil.